PUNISHMENT WITHOUT JUDGMENT: MEDIA-DRIVEN CRIMINALISATION AS COMMUNICATION POLICY AND ITS SYSTEMIC CHILLING EFFECTS ON FREEDOM OF EXPRESSION - Mufty, Abdul Malik; Nusawakan, Dwight (fakultas hukum universitas PGRI Semarang, 2026)
Contemporary criminal law increasingly operates beyond formal adjudication and enters the public sphere through media exposure and communicative practices. As criminal cases are framed and circulated through public narratives, criminalisation functions not only as a legal process but also as a mechanism of social meaning-making with regulatory consequences for behaviour and expression. This study aims to reconceptualise media-driven criminalisation as a form of communication policy that produces informal and reputational punishment outside judicial control. Employing a qualitative doctrinal–normative approach with conceptual and analytical orientation, the research examines criminalisation as a communicative legal construct and analyses its regulatory effects on freedom of expression through publicity, narrative framing, and reputational harm. The study finds that criminal law increasingly governs through symbolic and anticipatory mechanisms rather than through formal sanctions alone. Media exposure operates as an informal punitive process that shapes public judgment, normalises stigma, and induces anticipatory self-censorship, thereby generating systemic chilling effects on expressive freedom. These effects emerge even in the absence of judicial decisions and remain largely unaddressed by legal doctrines centred on direct state coercion. The originality of this research lies in its integration of criminal law, communication governance, and freedom of expression by positioning reputational harm and chilling effects as constitutive dimensions of criminalisation itself. The study contributes theoretically by extending the concept of punishment beyond coercive sanctions, and practically by highlighting the regulatory risks posed by media-driven criminalisation for procedural legitimacy, democratic participation, and expressive freedom.